Jawabanmu

2014-09-03T15:34:12+07:00
1.(7x + 15y) - (5x -9y)
 = 7x + 15y - 5x -9y
 = 7x - 5x + 15y -9y
 = 2x + 6y

2.(5y-3x-4) - (5x-3y+ 7)
 = 5y - 3x - 4 - 5x + 3y - 7
 = 5y + 3y - 3x - 5x - 4 - 7
 = 8y - (-8x) -(-11)
 = 8y + 8x + 11

3.(5x²-9xy-4y²) - (-x²+6xy +3y²)
 = 5x² - 9xy - 4y² + x² - 6xy - 3y²
 = 5x² + x² - 9xy -6xy - 4y² - 3y²
 = 6x² - (-15xy) - (-7y²)
 = 6x² +15xy + 7y²
2014-09-03T15:35:37+07:00
1. 7x + 15 y - 5x + 9y = 7x-5x+15y+9y = 2x + 24 y
2. 5y - 3x - 4  -5x + 3y -7 = 5y + 3 y - 3x - 5x - 4 - 7 = 8y - 8x - 11
3.  5x^{2} - 9xy -  4y^{2}  x^{2} - 6xy - 3 y^{2} 6 x^{2} - 15 xy -7 y^{2}